Literasi Media Terhadap Nilai Budaya Remaja Keturunan Tionghoa Di Kota Tangerang - Irmulansati Tomohardjo; Noviana Noviana (Bina Nusantara University, 2020)
This study aims to find out how media literacy is the cultural value of teenagers of Chinese descent in the China Benteng Tangerang area. This research uses a case study method, which describes social phenomena, with data collection techniques through in-depth interviews with three speakers. The research concept used is media literacy. The results showed that adolescents of Chinese descent in the China Benteng Tangerang region had cultural awareness and understanding of intercultural interaction. They are able to optimize new media for communication processes, interactions, information access needs and the process of disseminating cultural values. They are open to different cultures, and feel the value of nationalism becomes the main when its role as a member of the community, even though descendants peranakan.